Application Of Augmented Reality (Ar) In Android-Based Artificial Fiber Spinning Learning Media For Class Xi Students Tpsb Smk Texmaco Semarang - Irdha Yunianto; Sugiarto Sugiarto (University of Science and Computer Technology, 2023)
This research was motivated by limited depictions of objects in learning materials, lack of variation in the learning media used, lack of student interest in learning and students' final grades in productive subjects , especially in artificial fiber spinning material, with the average value of the material achieved not meeting the criteria. Minimum Completeness (KKM). This research is aimed at class This application was created with the aim of complementing the limitations of depicting objects in existing learning media, helping students learn the material more easily, improving student learning outcomes, and increasing media variations in learning. This research uses the Research and Development (RnD) method, using 6 of the 10 research stages, namely potential and problems, data collection, product design, design validation, design improvement and product testing. This research produces Artificial Fiber Spinning Learning Media that applies Augmented Reality (AR) for Class XI TPSB SMK Texmaco Semarang students as a learning aid. The final result of making this learning media is an application in Android application format, used on every Android-based mobile phone. As for the validity value from the media expert, the value obtained was 3.2, which was declared feasible, the results of the material expert validation test obtained the value 3.6, which was stated to be very feasibleand able to increase the average score in the class XI artificial fiber spinning subject at TPSB SMK Texmaco Semarang which originally 61.5% with 17 students who had not reached the KKM to 80.5% with 4 students who had not reached the KKM.